Conversaciones entre la familia y el equipo terapéutico en la discapacidad adquirida - Marín Padilla, Ernesto (2022)
This article examines a social reality of Colombian context, which indicates a larger number of people with acquired damages with the corresponding consequences and crisis faced by the families which must deal with a physical handicap. Besides, it invites the reader to reflect about the intervention process and in particular on the conversation process that patient families endure, when interacting with the professionals and health institutions. Studies point out the tendency of the members of the family to silence their ideas and feelings to protect the patient and it contributes to the impoverishment of the emotional contact. Furthermore, this article takes in account that most of health professionals, are centered only around the thechnicals aspects of the problem which hides the possibility to express and to understand the tension around such an event and invites to reason and discuss about the emotional context.